Defaults in Credit Agreements: How Are They Settled? - Rizky Auliandi; Mangatur Hadiputera Simanjuntak (Unnes Law Journal, 2020)
This study aims to determine whether the debtor has carried out his achievements as they should and knows the legal consequences for the debtor when trying to carry out his achievements more than the specified due date. This research is a normative or doctrinal research that is descriptive in nature using secondary data types. In this research, the data collection technique used is the study of literature. The results showed that Sujono, as the debtor and PT BPR Mranggen Mitra Persada as the creditor had carried out the credit agreement. By fulfilling the legal conditions of the agreement as stipulated in Article 1320 of the Civil Code, both subjective and objective terms, the agreement credit between PT BPR Mranggen Mitra Persada as the creditor and Sujono as the debtor is a legal agreement, but in credit repayments Sujono has an arrears of credit repayments calculated from the principal debt, interest, and costs incurred due to arrears. Since PT BPR Mranggen Mitra Persada filed a lawsuit with the Blora District Court, Sujono as a defendant had no good intention to attend the trial. The Panel of Judges decided to drop the verdict without the presence of the defendant called verstek. From this decision the defendant or Sujono fought against verstek or what was called the verzet. With respect to the verzet submitted by Sujono, the judge considered that the resistance was rejected by the Panel of Judges based on the consideration that Sujono had wrongly determined his legal subject and incorrectly determined the arguments of the resistance proposed by Sujono against PT BPR Mranggen Mitra Persada. Based on the decision of the Panel of Judges, Sujono is still considered to have defaulted and must fulfil his achievements.